2015
DOI: 10.1159/000369741
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Nose-Only Water-Pipe (Shisha) Smoking Exposure Accelerates Coagulation and Causes Cardiac Inflammation and Oxidative Stress in Mice

Abstract: Background/Aim: Water-pipe smoking (WPS) has acquired worldwide popularity, and is disseminating particularly rapidly in Europe and North America. However, little is known about the short-term cardiovascular effects of WPS. Methods: Presently, we assessed the short-term cardiovascular effects of nose-only exposure to mainstream WPS in BALB/c mice for 30 min/day for 5 consecutive days. Control mice were exposed to air. At the end of the exposure period, several cardiovascular endpoints were measured. Results: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 36 publications
6
45
1
Order By: Relevance
“…Betaine is a naturally occurring antioxidant agent which is found in a range of foods including wheat, shellfish, spinach, and sugar beets [20]. We have recently demonstrated that exposure to WPS for 5 days and one month increased blood pressure and thrombosis and induced inflammation and oxidative stress in the heart [14,15]. Therefore, in the present study we have assessed the subacute (2 weeks) effects of WPS on a comprehensive set of circulatory parameters and the possible palliative effect of betaine thereon.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Betaine is a naturally occurring antioxidant agent which is found in a range of foods including wheat, shellfish, spinach, and sugar beets [20]. We have recently demonstrated that exposure to WPS for 5 days and one month increased blood pressure and thrombosis and induced inflammation and oxidative stress in the heart [14,15]. Therefore, in the present study we have assessed the subacute (2 weeks) effects of WPS on a comprehensive set of circulatory parameters and the possible palliative effect of betaine thereon.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of SOD was measured according to the vendor's protocol (Cayman Chemicals, Michigan, USA). NADPH-dependent membrane lipid peroxidation was measured as thiobarbituric acid reactive substance using malonedialdehyde as standard (Sigma-Aldrich Fine Chemicals, St Louis, MO, USA) [27,36].…”
Section: Measurement Of Interleukin 6 (Il-6) Tumor Necrosis Factor αmentioning
confidence: 99%
See 2 more Smart Citations
“…27,37,45 In this model, the damage to endothelial cells causes the platelets to adhere at the site of endothelial damage and then aggregate. 27,37,45 The data of the present study show that acute IT administration of CeO 2 NPs induced a significant and dose-dependent shortening of the thrombotic occlusion time in pial arterioles and venules, indicating that CeO 2 NPs possess prothrombotic effects. Along with thrombosis in vivo, a dose-dependent and significant increase in the concentrations of the coagulation factor, fibrinogen, and PAI-1 in the plasma following acute exposure to CeO 2 NPs was found.…”
mentioning
confidence: 99%